Topical formulations of propranolol hydrochloride for infantile hemangioma – a comparative study on in vitro drug release - Kaurin, Milica; Bubić Pajić, Nataša (Archives of Pharmacy, 2022)
Oral administration of propranolol, the first-line treatment for infantile hemangioma, can sometimes cause several adverse effects, such as bradycardia, hypotension and hypoglycemia. Topical formulations of propranolol hydrochloride (PRO-CL) are considered as an appealing approach to selectively deliver the drug at the focal sites of disease, developing on/under the skin surface, and thus to address the abovementioned issues. The objective of this study was to rationalize the selection of PRO-CL topical formulations by investigating their in vitro drug release patterns. Conventional official bases (hydrophilic petrolatum ointment, amphiphilic cream, carbomer gel and carmellose gel) prepared according to Magistral formulae 2008 of the Republic of Serbia or DAC/NRF 2018 and two microemulsions were used as vehicles for PRO-CL-loaded (1%, w/w) formulations. In vitro drug release tests were performed using Franz diffusion cells equipped with polycarbonate membrane. The obtained results suggested that PRO-CL release was strongly influenced by the inner structure and physicochemical properties of the vehicles. The cumulative drug amount released from the tested samples over 24h ranged from 90.83 µg/cm2 to 3546.95 µg/cm2. PRO-CL liberation from lipophilic vehicle was extremely limited. The best results were obtained by using carmellose gel, making it the most promising formulation for PRO-CL dermal delivery. Interestingly, PRO-CL reached receptor medium from microemulsions was significantly lower than by utilization of both investigated gels. The outcomes of the current research may be of particular interest to pharmacists in community and hospital pharmacies. However, the effectiveness of the tested samples should be further verified on appropriate skin models.